P5 SUSTAINABLE LIFESTYLE: STRATEGIES TO STRENGTHEN STUDENTS' SOCIAL-EMOTIONAL AND LANGUAGE SKILLS: SUSTAINABLE LIFESTYLE P5: A STRATEGY FOR STRENGTHENING STUDENTS’ SOCIAL-EMOTIONAL AND LANGUAGE SKILLS - Sunarti; Arri Handayani; Bagus Ardi Saputro (SOSIOEDUKASI, 2025)
This study explores the impact of the Projek Penguatan Profil Pelajar Pancasila (P5) with the theme “Sustainable Lifestyle” on enhancing elementary students’ social-emotional and language skills. Conducted at SD Negeri Ungaran 01 using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. Prior to the project, students demonstrated low levels of emotional regulation and language proficiency. After the implementation of P5, improvements were evident. Students showed better emotional control, increased cooperation, and empathy. Language abilities also improved, as students became more confident in expressing ideas through speaking, reading, and writing. They engaged more actively in discussions and collaborative tasks. The contextual and project-based learning model in P5 was found to support students’ holistic development. The findings suggest that the P5 program, through its emphasis on meaningful, real-life themes and cooperative learning, can effectively strengthen both social-emotional and language competencies in alignment with the values of Pancasila